The Principle of Legality in the Perspective of Human Rights - Sri Ayuni, Mela; Dion, Dion; Cita Zulviah, Rifda; Nurtresna, Robby (Gayaku Publisher, 2022)
The principle of legality is a principle in law that is found in almost all of the constitutions of each country. The principle of legality is very important and must be maintained for the sake of certainty of rules in a country. If seen or reviewed properly, this principle of legality is a tool that aims to protect human rights for every individual and community group. As a jurisdiction, Indonesia always strives to uphold justice in order to achieve an orderly and peaceful life. However, with the existence of the principle of legality which is a written rule to determine that no action or action is prohibited and punished, if the act has been formulated in a law. The purpose of this writing is to find out how the principle of legality is in the perspective of human rights. This study uses a normative juridical method with a case approach and a statutory approach, the data used in this study is secondary data which is analyzed deductively. The results of this study are that the principle of legality has an important role in regulating the life of a group or society. One of the important roles of the principle of legality is to protect human rights, the role and function of the existence of the principle of legality is very influential in efforts to implement human rights regulations or better known as human rights. the life of the Indonesian people.